TYMSOS drives the proliferation, migration, and invasion of gastric cancer cells by regulating ZNF703 via sponging miR‐4739. (11th May 2021) - Gu, Yulan; Wan, Chuandan; Zhou, Guoqiang; Zhu, Jinlian; Shi, Zhiliang; Zhuang, Zhixiang
Abstract: Gastric cancer (GC) is a kind of malignancy originating from the epithelium of gastric mucosa. Long noncoding RNAs (lncRNAs) are tightly related to the GC progression. Herein, our research was meant to investigate a novel lncRNA thymidylate synthetase opposite strand ( TYMSOS ) in GC. Quantitative real‐time polymerase chain reaction was used to analyze TYMSOS expression in GC cells. 5‐Ethynyl‐2ʹ‐deoxyuridine, flow cytometry analysis, and transwell assay detected the influence of TYMSOS on GC cell proliferation, apoptosis, migration, and invasion. Subcellular fractionation and fluorescent in situ hybridization assays determined the cellular localization of TYMSOS in GC cells. Bioinformatics programs, RNA‐binding protein immunoprecipitation, RNA pull‐down, and luciferase reporter assays measured the molecular interplays of TYMSOS in GC cells. In brief, TYMSOS was highly expressed in GC cells, and TYMSOS silence inhibited GC cell proliferation, migration, and invasion while elevating cell apoptosis. Functionally, TYMSOS functioned as a competing endogenous RNA to posttranscriptionally modulate GC progression. TYMSOS interacted with miR‐4739 to regulate its target gene zinc finger protein 703 . Collectively, our study proved the tumor‐promoting role of TYMSOS in GC cells, which might offer the utility value for GC treatment.